Local Information Access for Search and Rescue Using Wireless Data Storage Mediums - Ergen, Esin; Talay, Sanem Sariel; Guven, Gursans; Avdan, Gurhan (American Society of Civil Engineers (ASCE), 2011)
After a natural disaster strikes buildings, it is vital to immediately retrieve the related local information for efficient search and rescue (S&R) operations. Although it seems convenient to store the required local information (e.g., information about neighborhood, buildings) in a centralized database, S&R teams usually cannot access centralized databases because the information infrastructure is usually damaged or overloaded immediately after a disaster. This paper describes the search and rescue data access point (SR-DAP) system that was designed for storing and retrieving the required local information in/from data storage units that are deployed at buildings. In the paper, the developed approach is presented, and two key technologies (i.e., radio-frequency identification (RFID) tags and wireless sensor nodes) that are used as local storage mediums in SR-DAP are empirically evaluated. The results of the field experiments show that current technologies can be effectively utilized in the developed system. However, comparison of the technologies highlights the fact that the current wireless sensor technology is advantageous over RFID technology.